Historical considerations and comments on the type series of Cyrtodactylus marmoratus Gray, 1831, with an updated comparative table for the bent-toed geckos of the Sunda Islands and Sulawesi - Mecke, Sven; Kieckbusch, Max; Hartmann, Lukas; Kaiser, Hinrich (Zootaxa, 2016)
Cyrtodactylus marmoratus Gray, 1831, a species of bent-toed gecko exhibiting a precloacal groove in males, was described on the basis of specimens collected by Heinrich Kuhl and Johan Conrad van Hasselt in Java, Greater Sunda Islands, Indonesia. Kluge (1985) subsequently designated a lectotype for C. marmoratus from a series of these specimens (i.e., syntypes), now housed in the herpetological collection at Naturalis (formerly the Rijksmuseum van Natuurlijke Historie; RMNH), Leiden, the Netherlands. Our work at Naturalis shows that the type series of C. marmoratus at RMNH actually comprises two sets of specimens, and that examination of specimens from one set or the other by different authors, including Kluge (1985), is responsible for some confusion surrounding the type series of this species. As a consequence, we present relevant morphological data for all 14 specimens constituting the type series of C. marmoratus at RMNH for the first time. The type status of two specimens of C. marmoratus in the collection at the Muséum National d’Histoire Naturelle, Paris, France, remains unresolved at present. Owing to the inconsistent naming and application of terms for some key characters (e.g., groove, sulcus, pit, hollow, depression) used in the diagnoses of Cyrtodactylus species, we here propose a set of novel and useful definitions that are supported by photographs. We also illustrate the sexually dimorphic expression of this character in C. marmoratus. Finally, we present a revised comparative table for the bent-toad geckos of the Sunda Islands and Sulawesi.